Weighted Approximation by Left Quasi-Interpolants of Derivatives of Gamma Operators (Communications in Mathematical Research, 2021)
In order to obtain much faster convergence, Müller introduced the left Gamma quasi-interpolants and obtained an approximation equivalence theorem in terms of $ω^{2r}_φ(f, t)_p$. Guoextended the Müller's results to $ω^{2r}_{φ^λ} (f, t)_∞$. In this paper we improve the previous results and givea weighted approximation equivalence theorem.